New Niobium Capacitors with Stable Electrical Parameters - H. Zillgen; M. Stenzel; W. Lohwasser (Active and Passive Electronic Components)
The replacement of the anode material in tantalum capacitors by a new generation of high CV niobium powders offers the possibility to get an economical alternative to tantalum for a wide range of applications. Due to the high CV potential of niobium powder there is also an alternative to low voltage aluminum electrolytic capacitors. We developed a new niobium capacitor which shows stable electrical values. By optimizing the structure of the dielectric and the cathodic layers as well as the process parameters we gained a capacitor which can be used up to 105 °C . Electrical characteristics and lifetest behavior of niobium capacitors out of 100 k–150 k CV/g powder will be discussed.